Tribological performance of silicone composite coatings filled with wax-containing microcapsules - Yang, J. L. (2013)
The effect of wax-containing microcapsules incorporated in silicone composite coatings deposited on aluminum (Al) alloy substrates on the tribological performance of the coatings was systematically investigated. The wax-containing microcapsules were prepared via in situ polymerization. The tribological behavior of the composite coatings was evaluated using ball-on-disk tribological test. It was found that the increase in microcapsule concentration in the composite coatings apparently reduced the friction coefficient of the coatings because the lubricant released from the broken microcapsules during the tribological test of the coatings lubricated the rubbing surfaces. The results showed that the silicone composite coatings rubbed by a smaller Cr6 steel ball (3 mm diameter) under a lower normal load (100 mN) produced higher friction coefficients via reduced complication of their underlying strong substrates compared to the same coatings tested against a larger Cr6 steel ball (6 mm diameter) under a higher normal load (1 N).